(untitled) (Revista Contexto & Educação, 2020)
This article presents partial results of Master’s Dissertation in the Graduate Program in Education in Science of a Federal University of the south of Brazil. It was asked: what curriculum of chemistry do teachers consider relevant and on what criteria is their choice based? It was heard teachers of Public Schools of the High School through a semistructured interview analyzed in light of the methodology of Discursive Textual Analysis (ATD in Portuguese). The general objective of the research was to recognize and interpret what the Chemistry Education community (Teachers) think about the Chemistry Curriculum in Basic Education in terms of conceptions, discourses and practices. Five categories of analysis were recognized, which are presented with propositions, and for this article it was chosen to present three of these categories: Innovative Curriculum; Curriculum Technicality and Curriculum as speech / definition. Among the results it was noticed that the teachers recognize that there is a need for an innovative curriculum, which relates the scientific contents to the daily life of the student, as well as, contemplate differentiated methodologies of work in the classroom; interpreted within the horizon of theoretical and practical conditions.